Biological cycle and comparative study of bioinsecticide efficiency on the Heliothis virescens (Lepidoptera:Noctuidae) borer in blueberry cultivation - Velásquez Ochoa, Edwin Ricardo (2023)
Objectives: To determine the biological cycle of H. virescens and the comparative efficiency of bioinsecticides of Bacillus thuringiensis (Bt) (native strain) with respect to Bt (Kurstaki strain) and nuclear polyhedrosis virus (NPV), on fifth instar larvae. Methodology: Postures and larvae of H. virescens were collected from agricultural farms in Huaral (Lima) and reared in the laboratory. The Bt and NPV strains were applied to fifth instar larvae under field conditions, evaluating larval mortality at 72 hours using Tukey's test with the Infostat software. Results: It was found that the life cycle of H. virescens was 77.78 ± 9.14 days with complete metamorphosis. Larval mortality was statistically similar (p> 0.05) with native Bt and Bt Kurstaki treatments, and NPV application outperformed (p< 0.05) both Bt treatments in fifth instar larval mortality. Conclusion: The life cycle of Heliothis virescens in blueberries has a complete metamorphosis with six larval stages ranging from 59-88 days and better control of fifth-instar larvae was obtained with NPV.